Enhancing Internal Control Procedures for Sustainable Small-Scale Businesses in Ekiti State - Adebayo, Adesodun; Ayeni-Agbaje, Abidoun; Taiwo, I. B; Fakiyesi, Oyindamola (Acta Universitatis Danubius. Œconomica, 2023)
This study investigates the influence of internal control procedures on the sustainability of small-scale businesses in Ekiti State. Specifically, it examines the impact of the control environment, control activities, risk assessment, information and communication, and monitoring on the longevity of small-scale enterprises in the region. The research adopts a survey-style descriptive research approach, with the population comprising all registered small companies in Ekiti State. According to the Ekiti State Micro, Small and Medium Enterprise Development Agency (DEMSMA), there are 44,065 registered small enterprises in the state. A sample size of 396 respondents is determined using Yamane's (1964) model. The study findings indicate that the sustainability of small-scale enterprises in Ekiti State is positively influenced by the control environment, risk assessment, and monitoring, whereas control activities and information and communication have insignificant effects. The coefficients and probability values for the significant variables are as follows: control environment (0.579, p=0.003 < 0.05), risk assessment (0.443, p=0.001 < 0.05), and monitoring (0.492, p=0.000 < 0.05). Conversely, control activities (0.050, p=0.525 > 0.05) and information and communication (0.070, p=0.374 > 0.05) have insignificant effects. Based on the analysis, it can be concluded that there is a statistically significant correlation between the sustainability of small-scale firms in Ekiti State, Nigeria, and internal control systems.